2018
DOI: 10.1007/s11356-018-2907-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental photochemical fate and UVC degradation of sodium levothyroxine in aqueous medium

Abstract: The synthetic hormone sodium levothyroxine (LTX) is one of the most prescribed drugs in the world and the most effective in hypothyroidism treatment. The presence of LTX in the environment has become a matter of major concern due to the widespread use of this hormone and by the fact that it is only partially removed in conventional water and sewage treatment plants. However, information regarding the photochemical fate of this hormone in environmental or engineered systems is scarce in the literature. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…drug substance) and in marketed drug products has been extensively investigated. [111][112][113][114][115][116] Our objective is to comprehensively review the factors affecting the stability of levothyroxine sodium when formulated as a solid oral dosage form. The term 'stability' encompasses both chemical and physical stability.…”
Section: Introductionmentioning
confidence: 99%
“…drug substance) and in marketed drug products has been extensively investigated. [111][112][113][114][115][116] Our objective is to comprehensively review the factors affecting the stability of levothyroxine sodium when formulated as a solid oral dosage form. The term 'stability' encompasses both chemical and physical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive use of the calculation engine first (the never publicly released Turbo Pascal-based version dates back to 2009), and of the full software later, has shown that APEX can be a powerful tool to model the photochemistry of aquatic systems and of the pollutants occurring in them. However, its potential can be exploited in full only if APEX is conceived as part of a whole environment, where kinetic measurements (to provide the input data) and photochemical modeling operate together [28][29][30]. Most photochemical degradation experiments carried out in the laboratory, even on real water samples, have the important drawback that it is not easy to extrapolate results obtained in the centimeters-deep water columns of photoreactors to the depths of several meters that are typical of natural water bodies [38].…”
Section: Wavelengthdependentmentioning
confidence: 99%
“…Moreover, it has been possible to extend the model applications from the originally foreseen simple systems (stationary and well mixed ones, such as overturning lakes) to more complex environments such as stratified lakes, rivers, and to include additional phenomena such as evaporative water concentration [27]. This remarkable flexibility comes at a price, however, because ease of use has never been the strong point of APEX.Despite this drawback, research groups located at the Institut de Chimie de Clermont-Ferrand (France) [16] and the Säo Paulo State University (Brasil) [28][29][30] have used APEX with very remarkable results, but the software diffusion took place to a lesser extent than initially hoped for. There have also been some indications that, at the moment, APEX may be more appreciated for its potential implications than actually used [31,32], thereby suggesting that user-friendliness may be an issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Levothyroxine sodium is administered orally as a thyroid hormone [3,4]. The oral bioavailability of levothyroxine is 65%, which is achieved if consumed 30 min to 1 h before breakfast on an empty stomach with a full glass of water [5,6] because of complex formation of levothyroxine with soybean products, sodium, calcium, and other minerals [7].…”
Section: Introductionmentioning
confidence: 99%